2019
DOI: 10.15252/embr.201947964
|View full text |Cite
|
Sign up to set email alerts
|

Mip6 binds directly to the Mex67 UBA domain to maintain low levels of Msn2/4 stress‐dependent mRNAs

Abstract: RNA‐binding proteins (RBPs) participate in all steps of gene expression, underscoring their potential as regulators of RNA homeostasis. We structurally and functionally characterize Mip6, a four‐RNA recognition motif (RRM)‐containing RBP, as a functional and physical interactor of the export factor Mex67. Mip6‐RRM4 directly interacts with the ubiquitin‐associated (UBA) domain of Mex67 through a loop containing tryptophan 442. Mip6 shuttles between the nucleus and the cytoplasm in a Mex67‐dependent manner and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 88 publications
(129 reference statements)
1
15
0
Order By: Relevance
“…We found a strong increase of this metabolite in the treated cells and a significant higher accumulation in the mutant. The metabolomics measurement was further confirmed by an independent analysis, where we measured trehalose levels in a double mutant lacking MIP6 and its yeast paralogue PES4 16 (Fig. 8c).…”
Section: Validation Of Biological Consistencysupporting
confidence: 53%
See 2 more Smart Citations
“…We found a strong increase of this metabolite in the treated cells and a significant higher accumulation in the mutant. The metabolomics measurement was further confirmed by an independent analysis, where we measured trehalose levels in a double mutant lacking MIP6 and its yeast paralogue PES4 16 (Fig. 8c).…”
Section: Validation Of Biological Consistencysupporting
confidence: 53%
“…Moreover, data are obtained for both WT and a mip6Δ mutant, in control and heat-shock induced conditions. Mip6 is an RNA-binding protein that participates in RNA export under stress 16 and consequently is informative of the contribution of post-transcriptional regulation to the adaptation of RNA levels to environmental changes. Taken together, the selection of yeast strains, growth conditions and omics experiments, creates a unique dataset to study the cross-talk between epigenetic, transcriptional and metabolic regulation in response to environmental cues.…”
Section: Background and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…We seized PAR-CLIP data, a technology that profiles RNA-protein interactions, to assess to which extent metabolic differences between strains might be caused by direct interaction with mip6. Mip6 is involved in RNA export from the nucleus and in stabilizing mRNAs in the cytosol through direct protein-RNA interactions [20]. PAR-CLIP data was available for WT yeast strain on the same heat stress conditions, indicating a total of 6685 mRNAs bound by mip6, with a small fraction of them (488) showing differential mip6 affinity after heat stress [20].…”
Section: Evaluating the Effect Of Mip6 Affinity On Metabolic Changesmentioning
confidence: 99%
“…In order to ensure cell survival under environmental stress, stress-induced transcripts need to be quickly exported to the cytoplasm for translation. Different scenarios have been proposed by which the export of stress-responsive transcripts is promoted [132,133]. Kim and coworkers have shown that Sgf73 interacts with the essential mRNA export factor Yra1p under environmental stress conditions and thereby facilitates the prompt translocation of the stress-induced mRNAs [131].…”
Section: Alternative Roles Of Sgf73/ataxin-7 In Mrna Metabolismmentioning
confidence: 99%